2011
DOI: 10.1152/ajpregu.00421.2010
|View full text |Cite
|
Sign up to set email alerts
|

Phagocyte-like NADPH oxidase promotes cytokine-induced mitochondrial dysfunction in pancreatic β-cells: evidence for regulation by Rac1

Abstract: Reactive oxygen species (ROS) are important mediators of cellular signal transduction cascades such as proliferation, migration, and apoptosis. Chronic exposure of isolated β-cells to proinflammatory cytokines elevates intracellular oxidative stress leading to the demise of pancreatic β-cells culminating in the onset of diabetes. Although the mitochondrial electron transport chain is felt to be the primary source of ROS, several lines of recent evidence suggest that phagocyte-like NADPH oxidase plays a central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
85
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 30 publications
10
85
0
Order By: Relevance
“…Available evidence suggests that a protein kinase C-sensitive phosphorylation of p47 phox leads to its translocation to the membrane fraction (3). It has also been shown that functional activation of Rac1 (Rac1.GTP) is vital for the holoenzyme assembly and activation of Nox in insulin-secreting cells (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence suggests that a protein kinase C-sensitive phosphorylation of p47 phox leads to its translocation to the membrane fraction (3). It has also been shown that functional activation of Rac1 (Rac1.GTP) is vital for the holoenzyme assembly and activation of Nox in insulin-secreting cells (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of recent evidence implicated roles for reactive oxygen species (ROS) in metabolic dysfunction of the islet ␤-cell under the duress of glucolipotoxicity, cytokines, and ceramide (26,38,39). It has been shown that increased ROS generation seen under the above experimental conditions is derived from the activation of phagocyte-like NADPH oxidase (Nox), since inhibition of this enzyme by selective inhibitors [e.g., diphenyleneiodonium chloride (DPI) or apocynin] or transfection of short interfering RNA (siRNA) against individual subunits of Nox (e.g., p47 phox ) significantly attenuated deleterious effects of aforementioned noxious stimuli (38,39).…”
mentioning
confidence: 99%
“…In addition to the above mentioned strategies for attenuating oxidative stress, inhibitors blocking Tiam1/Rac1/Nox signaling axis, 57,94,106 polyphenolic extracts supplementation, 107 stress activated kinase inhibitors, [108][109][110][111] and angiotensin receptor antagonists 112 have proven efficaciously to reduce oxidative stress and improve islet β-cell function.…”
Section: Potential Therapeutic Targets and Interventional Modalitiesmentioning
confidence: 99%
“…91 In addition, studies have also implicated Nox in metabolic dysfunction of the islet β-cell under conditions of glucolipotoxicity and exposure to cytokines. 57,94 Generation of ROS under these conditions appears to be largely due to the activation of Nox, since inhibition of …”
mentioning
confidence: 99%
See 1 more Smart Citation